Uji Efektivitas Konsentrasi dan Lama Perendaman Larutan KNO₃ terhadap Daya Perkecambahan dan Viabilitas Benih Padi (Oryza sativa L.) Kedaluwarsa Varietas INPARI-32 - Amara Anggelliya; Putra Utama; Julio Eiffelt Rossafelt Rumbiak; Zahratul Millah (Program Studi Agroteknologi INSTIPER, 2026)
In rice, germination and early seedling growth are significantly influenced by seed viability. Viability is decreased by seed deterioration during storage, especially in older seeds. The purpose of this study was to ascertain how soaking time and potassium nitrate (KNO₃) concentration affected the germination and viability of old rice seeds (Oryza sativa L.) of the Inpari-32 variety. KNO₃ concentrations (0%, 1%, 2%, and 3%) and soaking times (24, 30, and 36 hours) were the two elements that determined the experiment's Completely Randomised Design (CRD). The percentage of normal seedlings, aberrant seedlings, vigour index, germination percentage, and non-germinated seeds were among the parameters noted. The results indicated that KNO₃ concentration significantly increased germination, with the highest percentage of normal seedlings obtained at 3% KNO₃ showing an increase of (48.33%) compared to the control and followed by 2% KNO₃ with an increase of (47.77%), compared to the control (32.22%). The length of the soaking period had a significantly significant impact; 36 hours produced the highest germination percentage (59.58%), followed by 30 hours (47.30%) and 24 hours (15.90%). There was no discernible relationship between the amount of KNO₃ and the length of soaking. While longer soaking times improved water imbibition and triggered physiological processes, the administration of KNO₃ increased seed metabolic activity. In conclusion, old rice seeds' viability and vigour were successfully increased by KNO₃ concentrations of 2-3% and a 36-hour soaking period; however, the improvement was insufficient to reach a high vigour category.